STRUKTUR DAN FUNGSI SOSIAL UNGKAPAN LARANGAN TENTANG KEMATIAN DAN ADAT PEMAKAMAN MASYARAKAT DI JORONG KOTO PANJANG KENAGARIAN SUNGAI TARAB KECAMATAN SUNGAI TARAB KABUPATEN TANAH DATAR - Fahriandari, Femmy; WS, Hasanuddin; Zulfadhli, Zulfadhli (Universitas Negeri Padang, 2018)
This article is purposed to describe social structure and function of prohibitive proverb about death and funeral custom of Jorong Koto Panjang society at Sungai Tarab village Tanah Datar regency. Literature used in this study was folklor theory. This study was qualitative study with descriptive method and content analysis which was explained facts that determined in study object to describe structure and function of prohibitive proverb about death and funeral custom of Jorong Koto Panjang society at Sungai Tarab village Tanah Datar regency. this study was conducted by anlysis study object with these measures: (1) describe structure of prohibitive proverb, (2) describe funcion of social believe in prohibitive proverb. Structure in this prohibitive proverb consisted of two parts which were double structure and triplet structure. Double structure was causal and effect, and triplet structure was sign, conversion, and effect. next, function of social believe was used to increase faith, imaginary projection system, education, prohibition, and instruction. based on data analysis, the conclusion was prohibitive proverb about death and funeral custom of Jorong Koto Panjang society at Sungai Tarab village Tanah Datar regency had 36 proverbs that consisted of 34 double structure proverbs and 36 triplet structure proverbs with function as prohibition and increasing faith, four function as imaginary projection system, 12 as education, and 31 as instruction.Keywords: structure, social function, expression of prohibition